Pemantauan dan Pengendalian Parameter Akuaponik Menggunakan Representational State Transfer Application Programming Interface - Helmy; Athadhia Febyana; Agung Al Rasyid; Arif Nursyahid; Thomas Agung Setyawan; Ari Sriyanto Nugroho (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Aquaponics is a combination of aquaculture and hydroponics. One of the hydroponic systems is a drip system. Parameters that need to be considered in aquaponic culture include the acidity of nutrient solution (pH), water temperature, and nutrient solution showed by Total Dissolved Solids (TDS). Plant nutrition is obtained from fish manure which contains nitrogen. Therefore, monitoring pH, TDS, and temperature in realtime and controling soil moisture in aquaponic plants are needed so the plants do not lack nutrients. Representational State Transfer Application Programming Interface (REST API) is used to receive threshold values by farmers through the website and also sends soil moisture values and aquaponics parameters of pH, temperature, and TDS to server. Delay test of the monitoring and controling system is needed to determine the device’s reliability of transmission data. Notification by email is sent to farmer if the soil moisture value is less than the threshold. The result shows that the system can send notification by email to farmer when the soil moisture value was less than the threshold, the average delay of the node-gateway monitor is 6.01 s, while the average delay of gateway-server monitor 10.02 s, and the average delay of server-gateway control is 92.55 s.